Screening for antimicrobial activities in soil fungal isolated from Kubah National Park - Yue, Keong Choon (Universiti Malaysia Sarawak, UNIMAS, 2012)
A study was carried out on soil samples collected from Kubah National Park in order to discover novel antibiotics produced by soil microbes. Twenty one samples of soil were analyzed for antimicrobial producing microbes. The test bacteria used in this study were Escherichia coli, Listeria monocytogenes, Salmonella enteritidis and Klebsiella pneumoniae. Six fungal isolates (P550 AI a iv, P550 AI b iv, P550 AI c iii, P550 AI d iv, P550 AII a iv, P550 AII b iv) showed strong antibacterial activity against different strains of test bacteria during antibiotic activity screening using agar overlay techniques in the preliminary screening followed by secondary screening. A total of 3 fungal isolates (P550AIa, P550AIb, P550AIc) were selected to undergo antibiotics susceptibility testing and characterization. These 3 fungal isolates showed MIC value and produced inhibition zone compared to the positive control (5× dilutions of penicillin-streptomycin solution). The 3 fungal isolates were subjected to thin layer chromatography and bioautography to characterize their antimicrobial active compound. Three fungal isolates were subjected to Polymerase Chain Reaction (PCR) and gel electrophoresis, however only P550AIb showed band on gel electrophoresis. Upon identification, P550AIb was identified as Penicillium verruculosum after being sequenced. All the fungal isolates could be used to produce antimicrobial compound.